Governing the world : the history of an idea - Mazower, Mark. (New York : Penguin Books, 2013)
"A history of the project of world government, from the first post-Napoleonic visions of the brotherhood of man to the current crisis of global finance"-- Provided by publisher.
Includes bibliographical references (p. [429]-455) and index.
Keywords: International organization; Uluslararası organizasyonlar; International cooperation; International relations; Uluslararası ilişkiler; World politics; Dünya politikası